(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Teismo/ateismo: l’eredità storica di una presunta dicotomia - 2. La polifonia “in crescendo” del nuovo panorama religioso - 3. Confessione religiosa, esser(lo) o non esser(lo): questo è il dilemma - 4. Associazioni ateiste: minoranze religiose escluse? Osservazioni conclusive. Are atheists a religious minority? The legal status of atheism in Italy and in some countries of the European Union. ABSTRACT: “Religion” and “confession” are terms without an established definition in sociology and the legal sciences. The absence of a definition allows us to consider the religious phenomenon in its complexity, including both belief and unbelief. The analysis tries to understand if a common legal discipline is possible for theistic and non-theistic phenomenon. The analysis focuses on the legal status of non-believers minority in Italy and in some countries of the European Union.